Could Interventional Radiological Therapies Offer a Safer Alternative as We Emerge from COVID-19 Pandemic? - Shuvro H. Roy-Choudhury; Gireesh Warawdekar (Journal of Clinical Interventional Radiology ISVIR)
The ongoing SARS-CoV-2 (COVID-19) pandemic poses a major risk to health care delivery all around the world and also poses significant risks to the public and health care workers (HCWs). Surgical procedures, particularly elective procedures, have been cancelled or deferred due to increased risks associated with surgery and anesthesia both to the patient and the HCWs as well as to allocate resources to treat infected patients. This is particularly true for patients with comorbidities and cancer. As countries emerge from this pandemic, a phased return to conventional surgical procedures is being proposed, with emphasis on procedures performed in ambulatory settings and avoiding endotracheal intubation, where possible. Interventional radiological (IR) procedures offer a unique advantage in this setting, as these procedures are often performed with local or regional anesthesia with shorter hospital stay. In this brief communication, we outline the current opinion on surgical risks and guidelines and suggest areas where interventional therapies may offer an advantage to the multidisciplinary team and patient.